PENTINGNYA STRATEGI MANAJEMEN DAN EDUKASI KEUANGAN BAGI GENERASI MUDA DALAM PENGEMBANGAN DUNIA BISNIS - Mirda, Rizyana; Utami, Budi; Wahyono, Dwi; Nurhanimah, Nurhanimah; Siregar, Achiruddin (Batara Wisnu : Indonesian Journal of Community Services, 2025)
The younger generation plays a strategic role in economic growth in the digital era. However, low levels of financial education and a lack of strategic understanding of business management hinder young people's business development. This community service program aims to emphasize strategic management skills and financial education, as well as business readiness, through education, workshops, and mentoring. Methods used include seminars and training. Results indicate an increased understanding of management strategies and the use of financial records in business planning, and an increased motivation to become entrepreneurs.